2008
DOI: 10.1590/s0100-204x2008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Detection of siderophores in endophytic bacteria Methylobacterium spp. associated with Xylella fastidiosa subsp. pauca

Abstract: -The objective of this work was to study the production of siderophores by endophytic bacteria Methylobacterium spp., which occupy the same ecological niche as Xylella fastidiosa subsp. pauca (Xfp) in citrus plants. The siderophore production of Methylobacterium strains was tested according to chromeazurol agar assay test (CAS), Csáky test (hydroxamate-type) and Arnow test (catechol-type). In addition, the ability of Xfp to use siderophores, in vitro, produced by endophytic bacteria as source of iron, was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 34 publications
2
27
0
3
Order By: Relevance
“…Os mecanismos de promoção de crescimento pelas bactérias epifíticas e endofíticas incluem diferentes ações, como a fixação biológica de nitrogênio (KuKlinsky-Sobral et al, 2004), solubilização de fosfatos (Chabot et al, 1998;Verma et al, 2001), biossíntese de fito-hormônios (Lucangeli & Bottini, 1997), influência na atividade enzimática da 1-aminociclopropano 1-carboxilato (ACC) deaminase (Rothballer at al., 2008), controle biológico (Byrne et al, 2005), síntese de sideróforos (Lacava et al, 2008) e indução de resistência sistêmica a patógenos na planta hospedeira (Kloepper et al, 1999 Efeitos positivos da inoculação de bactérias promotoras de crescimento foram verificados na abacaxicultura, principalmente quando as bactérias inoculadas também são fixadoras de nitrogênio atmosférico (Weber et al, 2003). Já foram isoladas de abacaxizeiros bactérias diazotróficas pertencentes aos gêneros Burkholderia (Weber et al, 1999), Acetobacter (Tapia-Hernández et al, 2000) e Asaia (Weber et al, 2003).…”
Section: Introductionunclassified
“…Os mecanismos de promoção de crescimento pelas bactérias epifíticas e endofíticas incluem diferentes ações, como a fixação biológica de nitrogênio (KuKlinsky-Sobral et al, 2004), solubilização de fosfatos (Chabot et al, 1998;Verma et al, 2001), biossíntese de fito-hormônios (Lucangeli & Bottini, 1997), influência na atividade enzimática da 1-aminociclopropano 1-carboxilato (ACC) deaminase (Rothballer at al., 2008), controle biológico (Byrne et al, 2005), síntese de sideróforos (Lacava et al, 2008) e indução de resistência sistêmica a patógenos na planta hospedeira (Kloepper et al, 1999 Efeitos positivos da inoculação de bactérias promotoras de crescimento foram verificados na abacaxicultura, principalmente quando as bactérias inoculadas também são fixadoras de nitrogênio atmosférico (Weber et al, 2003). Já foram isoladas de abacaxizeiros bactérias diazotróficas pertencentes aos gêneros Burkholderia (Weber et al, 1999), Acetobacter (Tapia-Hernández et al, 2000) e Asaia (Weber et al, 2003).…”
Section: Introductionunclassified
“…Lacava et al (2008) reported that many plants are able to use the siderophores produced by bacterial endophytes as main iron source. In addition, siderophores can inhibit the growth of pathogenic microorganisms, therefore they acts as a pathogen biocontrol agent and indirectly stimulate the growth of plant (Glick, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly Methylobacterium spp. found to be positive towards the hydroxamate-type of siderophore production (Csáky assay), but negative towards the catechol-type siderophores production (Arnow assay) (Lacava et al, 2008). Senthilkumar et al, (2009) isolated a total of 137 endophytic bacteria from the surface sterilized root, stem and of soybean and screened their siderophore production ability.…”
Section: Siderophores Productionmentioning
confidence: 99%